O papel do engajamento na construção do discurso sobre privatização em notícias acerca da polêmica de adesão de hospitais universitários federais à EBSERH - Rossi, Ariane de Fatima Escobar (2017)
In the current scenario of political and economical crisis witnessed in Brazil, this year of 2017, the privatization comes as one of the big issues which causes controversy nowadays (GEE, 2007) and one of the alternatives found by governments to obtain more administrative rationality, operational efficiency and cost-cutting. In this context, society is increasingly more and more influenced by media, which becomes a medium with strong persuasive power, influencing beliefs, values, relationships and social identities (FAIRCLOUGH, 1995), as taking positions is almost imposed to people. In the year of 2011, the launched of the Provisional Measure (MP) 520, which created the Brazilian Hospital Services Company (EBSERH), aiming to restructuring the University Federal Hospitals (HUFs), caused a big debate in the media. The controversy is centered on the EBSERH‟s deployment in the HUs, because, although the company is considered public, it has a private capital and the community fears that the adhesion could be the synonym of privatization. From this context, the objective of this study is to investigate to what extent the linguistic marks of engagement convoked by the journalists concur for the attribution of voices in discourses about privatization in news on the controversy of the administration of HUFs by EBSERH. The corpus of this research is formed by 187 news from four Brazilian regions: Southeast, Northeast, South and Center-West, gathered from the website Guia de Mídia, between 2011 and 2016. We identified occurrences of engagement-attribution, based on the categories of the Appraisal System (MARTIN; WHITE, 2005), that were divided by region, city, university and, then, classified according to the following lexical-grammar categories which also guided the analysis: 1) voices and their positioning and 2) employed processes (CALDAS-COULTHARD, 1994; HALLIDAY, MATTHIESSEN, 2014), ways of projection (quote, report, angle circumstance and evoked quote) and type of engagement-attribution (MARTIN; WHITE, 2005). The results show that there is a contraction masked of expansion, because the journalists convoke some voices and almost exclude others, not opening the dialogical space to alternative positioning. The choice of sources and its positioning, of the lexical-grammar exponents and, consequently, the predominance of the use of acknowledge by journalists reflect different alignments of theses authors in each region, in order to achieve solidarity in relation to the putative readers.